Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Sex demographics alter the effect of habitat structure on predation by a temporary pond specialist - Ross N. Cuthbert; Tatenda Dalu; Ryan J. Wasserman; Olaf L. F. Weyl; P. William Froneman; Amanda Callaghan; Jaimie T. A. Dick (Hydrobiologia, 2020)
Habitat structure can profoundly influence interaction strengths between predators and prey. Spatio-temporal habitat structure in temporary wetland ecosystems is particularly variable because of fluctuations in water levels and vegetation colonisation dynamics. Demographic characteristics within animal populations may also alter the influence of habitat structure on biotic interactions, but have remained untested. Here, we investigate the influence of vegetation habitat structure on the consumption of larval mosquito prey by the calanoid copepod Lovenula raynerae , a temporary pond specialist. Increased habitat complexity reduced predation, and gravid female copepods were generally more voracious than male copepods in simplified habitats. However, sexes were more similar as habitat complexity increased. Type II functional responses were exhibited by the copepods irrespective of habitat complexity and sex, owing to consistent high prey acquisition at low prey densities. Attack rates by copepods were relatively unaffected by the complexity gradient, whilst handling times lengthened under more complex environments in gravid female copepods. We demonstrate emergent effects of habitat complexity across species demographics, with predation by males more robust to differences in habitat complexity than females. For ecosystems such as temporary ponds where sex-skewed predator ratios develop, our laboratory findings suggest habitat complexity and sex demographics mediate prey risk.

Regulation of biosimilar medicines and current perspectives on interchangeability and policy - J. O’Callaghan; S. P. Barry; M. Bermingham; J. M. Morris; B. T. Griffin (European Journal of Clinical Pharmacology, 2019)

Salvelinus namaycush spawning substratum attracts egg predators and opportunists through chemosensory cues - B. A. Wasylenko; D. T. Callaghan; P. J. Blanchfield; G. G. Pyle (Journal of Fish Biology, 2014)
Two separate field experiments were conducted in a series of small boreal lakes to test for the attraction of egg predators to lake trout Salvelinus namaycush spawning shoals and subsequently to determine whether chemosensory cues attract egg predators to these sites. In the first experiment, minnow traps set on spawning sites captured significantly more egg predators than those set on structurally similar non‐spawning sites. Captures of slimy sculpin Cottus cognatus , common shiner Luxilus cornutus , blacknose shiner Notropis heterolepis and virile crayfish Orconectes virilis were more than double on spawning sites relative to non‐spawning sites for the two study lakes. To test whether chemosensory cues could attract egg predators to S. namaycush spawning sites, paired minnow traps were placed on eight to 10 sites in each of the three study lakes; one trap contained visually concealed S. namaycush spawning substratum and the other with visually concealed non‐spawning substratum. Traps containing spawning substratum consistently captured more fish and had higher mean daily catches than those that contained non‐spawning substratum. The combined results demonstrate a greater prevalence of egg predators on S. namaycush spawning shoals that appears to be the result of chemosensory attraction to spawning substratum.

Towards a unified paradigm for sequence‐based identification of fungi - Urmas Kõljalg; R. Henrik Nilsson; Kessy Abarenkov; Leho Tedersoo; Andy F. S. Taylor; Mohammad Bahram; Scott T. Bates; Thomas D. Bruns; Johan Bengtsson‐Palme; Tony M. Callaghan; Brian Douglas; Tiia Drenkhan; et al. (Molecular Ecology, 2013)
The nuclear ribosomal internal transcribed spacer ( ITS ) region is the formal fungal barcode and in most cases the marker of choice for the exploration of fungal diversity in environmental samples. Two problems are particularly acute in the pursuit of satisfactory taxonomic assignment of newly generated ITS sequences: (i) the lack of an inclusive, reliable public reference data set and (ii) the lack of means to refer to fungal species, for which no Latin name is available in a standardized stable way. Here, we report on progress in these regards through further development of the UNITE database ( http://unite.ut.ee ) for molecular identification of fungi. All fungal species represented by at least two ITS sequences in the international nucleotide sequence databases are now given a unique, stable name of the accession number type (e.g. H ymenoscyphus pseudoalbidus | GU 586904| SH 133781.05 FU ), and their taxonomic and ecological annotations were corrected as far as possible through a distributed, third‐party annotation effort. We introduce the term ‘species hypothesis’ ( SH ) for the taxa discovered in clustering on different similarity thresholds (97–99%). An automatically or manually designated sequence is chosen to represent each such SH. These reference sequences are released ( http://unite.ut.ee/repository.php ) for use by the scientific community in, for example, local sequence similarity searches and in the QIIME pipeline. The system and the data will be updated automatically as the number of public fungal ITS sequences grows. We invite everybody in the position to improve the annotation or metadata associated with their particular fungal lineages of expertise to do so through the new Web‐based sequence management system in UNITE .

A Design Space Verification Protocol for a Small Molecule Drug Substance - Timothy J. N. Watson; Holly Bonsignore; Eileen A. Callaghan-Manning; Stephen T. Colgan; Paul Fitzsimons; Thomas P. Garcia; John G. Groskoph; Michael P. Lynch; Roger Nosal; Megan E. McMahon; Robert A. Singer; Nicholas M. Thomson; et al. (Journal of Pharmaceutical Innovation, 2013)

Seasonal climate manipulations have only minor effects on litter decomposition rates and N dynamics but strong effects on litter P dynamics of sub-arctic bog species - R. Aerts; T. V. Callaghan; E. Dorrepaal; R. S. P. van Logtestijn; J. H. C. Cornelissen (Oecologia, 2012)

Extreme winter warming events more negatively impact small rather than large soil fauna: shift in community composition explained by traits not taxa - S. Bokhorst; G. K. Phoenix; J. W. Bjerke; T. V. Callaghan; F. Huyer‐Brugman; M. P. Berg (Global Change Biology, 2012)
Extreme weather events can have negative impacts on species survival and community structure when surpassing lethal thresholds. Extreme winter warming events in the A rctic rapidly melt snow and expose ecosystems to unseasonably warm air (2–10 °C for 2–14 days), but returning to cold winter climate exposes the ecosystem to lower temperatures by the loss of insulating snow. Soil animals, which play an integral part in soil processes, may be very susceptible to such events depending on the intensity of soil warming and low temperatures following these events. We simulated week‐long extreme winter warming events – using infrared heating lamps, alone or with soil warming cables – for two consecutive years in a sub‐ A rctic dwarf shrub heathland. Minimum temperatures were lower and freeze‐thaw cycles were 2–11 times more frequent in treatment plots compared with control plots. Following the second event, A cari populations decreased by 39%; primarily driven by declines of P rostigmata (69%) and the M esostigmatic nymphs (74%). A community‐weighted vertical stratification shift occurred from smaller soil dwelling (eu‐edaphic) C ollembola species dominance to larger litter dwelling (hemi‐edaphic) species dominance in the canopy‐with‐soil warming plots compared with controls. The most susceptible groups to these winter warming events were the smallest individuals ( P rostigmata and eu‐edaphic C ollembola). This was not apparent from abundance data at the C ollembola taxon level, indicating that life forms and species traits play a major role in community assembly following extreme events. The observed shift in soil community can cascade down to the micro‐flora affecting plant productivity and mineralization rates. Short‐term extreme weather events have the potential to shift community composition through trait composition with potentially large consequences for ecosystem development.

Ecosystem responses to increased precipitation and permafrost decay in subarctic Sweden inferred from peat and lake sediments - U. KOKFELT; P. ROSÉN; K. SCHONING; T. R. CHRISTENSEN; J. FÖRSTER; J. KARLSSON; N. REUSS; M. RUNDGREN; T. V. CALLAGHAN; C. JONASSON; D. HAMMARLUND (Global Change Biology, 2009)
Recent accelerated decay of discontinuous permafrost at the Stordalen Mire in northern Sweden has been attributed to increased temperature and snow depth, and has caused expansion of wet minerotrophic areas leading to significant changes in carbon cycling in the mire. In order to track these changes through time and evaluate potential forcing mechanisms, this paper analyses a peat succession and a lake sediment sequence from within the mire, providing a record for the last 100 years, and compares these with monitored climate and active layer thickness data. The peat core was analysed for testate amoebae to reconstruct changes in peatland surface moisture conditions and water table fluctuations. The lake sediment core was analysed by near infrared spectroscopy to infer changes in the total organic carbon (TOC) concentration of the lake‐water, and changes in δ 13 C and C, N and δ 15 N to track changes in the dissolved inorganic carbon (DIC) pool and the influence of diagenetic effects on sediment organic matter, respectively. Results showed that major shifts towards increased peat surface moisture and TOC concentration of the lake‐water occurred around 1980, one to two decades earlier than a temperature driven increase in active layer thickness. Comparison with monitored temperature and precipitation from a nearby climate station indicates that this change in peat surface moisture is related to June–September (JJAS) precipitation and that the increase in lake‐water TOC concentration reflects an increase in total annual precipitation. A significant depletion in 13 C of sediment organic matter in the early 1980s probably reflects the effect of a single or a few consecutive years with anomalously high summer precipitation, resulting in elevated DIC content of the lake water, predominantly originating from increased export and subsequent respiration of organic carbon from the mire. Based on these results, it was not possible to link proxy data obtained on peat and lake‐sediment records directly to permafrost decay. Instead our data indicate that increased precipitation and anomalously high rainfall during summers had a significant impact on the mire and the adjacent lake ecosystem. We therefore propose that effects of increased precipitation should be considered when evaluating potential forcing mechanisms of recent changes in carbon cycling in the subarctic.

Role of lipase in Burkholderia cepacia complex (Bcc) invasion of lung epithelial cells - T. Mullen; K. Markey; P. Murphy; S. McClean; M. Callaghan (European Journal of Clinical Microbiology & Infectious Diseases, 2007)

Climate change has only a minor impact on nutrient resorption parameters in a high-latitude peatland - R. Aerts; J. H. C. Cornelissen; R. S. P. van Logtestijn; T. V. Callaghan (Oecologia, 2007)

Microbial communities of Solanum tuberosum and magainin-producing transgenic lines - M. O’Callaghan; E. M. Gerard; N. W. Waipara; S. D. Young; T. R. Glare; P. J. Barrell; A. J. Conner (Plant and Soil, 2005)

Effects of experimentally imposed climate scenarios on flowering phenology and flower production of subarctic bog species - R. Aerts; J. H. C. Cornelissen; E. Dorrepaal; R. S. P. Van Logtestijn; T. V. Callaghan (Global Change Biology, 2004)
Climate scenarios for high‐latitude areas predict not only increased summer temperatures, but also larger variation in snowfall and winter temperatures. By using open‐top chambers, we experimentally manipulated both summer temperatures and winter and spring snow accumulations and temperatures independently in a blanket bog in subarctic Sweden, yielding six climate scenarios. We studied the effects of these scenarios on flowering phenology and flower production of Andromeda polifolia (woody evergreen) and Rubus chamaemorus (perennial herb) during 2 years. The second year of our study (2002) was characterized by unusually high spring and early summer temperatures. Our winter manipulations led to consistent increases in winter snow cover. As a result, average and minimum air and soil temperatures in the high snow cover treatments were higher than in the winter ambient treatments, whereas temperature fluctuations were smaller. Spring warming resulted in higher average, minimum, and maximum soil temperatures. Summer warming led to higher air and soil temperatures in mid‐summer (June–July), but not in late summer (August–September). The unusually high temperatures in 2002 advanced the median flowering date by 2 weeks for both species in all treatments. Superimposed on this effect, we found that for both Andromeda and Rubus , all our climate treatments (except summer warming for Rubus ) advanced flowering by 1–4 days. The total flower production of both species showed a more or less similar response: flower production in the warm year 2002 exceeded that in 2001 by far. However, in both species flower production was only stimulated by the spring‐warming treatments. Our results show that the reproductive ecology of both species is very responsive to climate change but this response is very dependent on specific climate events, especially those that occur in winter and spring. This suggests that high‐latitude climate change experiments should focus more on winter and spring events than has been the case so far.

Plant virus surveys on the island of New Guinea and adjacent regions of northern Australia - R. I. Davis; J. E. Thomas; L. A. McMichael; R. G. Dietzgen; B. Callaghan; A. P. James; T. G. Gunua; S. Rahamma (Australasian Plant Pathology, 2002)

Confidence Interval Criteria for Assessment of Dose Proportionality - Brian P. Smith; Francois R. Vandenhende; Karl A. DeSante; Nagy A. Farid; Pamela A. Welch; John T. Callaghan; S. Thomas Forgue (Pharmaceutical Research, 2000)

Symposia lectures - F. Parak; A. Ostermann; G. U. Nienhaus; Nobuo Niimura; William A. Eaton; Stephen J. Hagen; Eric R. Henry; James Hofrichter; Gouri Jas; Lisa Lapidus; Victor Muñoz; Chih-chen Wang; et al. (Journal of Biosciences, 1999)

A non-invasive measurement of phloem and xylem water flow in castor bean seedlings by nuclear magnetic resonance microimaging - W. Kckenberger; J. M. Pope; Y. Xia; K. R. Jeffrey; E. Komor; P. T. Callaghan (Planta, 1997)